Effect of indomethacin on clinical progress and renal function in cystinosis. - Haycock, G B (1982)
Three children with nephropathic cystinosis were treated with indomethacin 3 mg/kg a day for periods ranging from 9 to 18 months. The drug produced worthwhile clinical improvement in all, with marked beneficial effects on polyuria, polydipsia, and general wellbeing. Clearance studies performed under conditions of maximal water diuresis showed that proximal tubular sodium reabsorption was increased in all children, with consequent reduction in sodium delivery to the distal nephron leading to reduced free water clearance and distal tubular cation exchange. Plasma sodium and potassium concentrations became normal in all patients, with improvement in phosphate and bicarbonate concentrations in one. Renal function continued to deteriorate, but without obvious acceleration of the process by the drug. We were unable to demonstrate a beneficial effect on growth; nevertheless, indomethacin is a useful adjunct to the symptomatic treatment of children with severe nephropathic cystinosis.